Deskripsi Kemampuan Berpikir Kreatif Matematis Mahasiswa Ditinjau dari Kemampuan Awal Matematika - Nurrahmah, Arfatin; Agustina, Lasia (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2021)
This research aims to describe students' ability in mathematical creative thinking in terms of the initial ability of mathematics, in the set material, relationship of functions, and mathematical logic, in the course Introduction to Basic Mathematics (PDM). Qualitative descriptive is used as a research method and is carried out at Indraprasta University PGRI Jakarta. Three students who took the Introductory Basic Mathematics course in the odd semester of the academic year 2020/2021, were selected as research subjects. The taking of the subject is done using purposive sampling. The instruments used are tests of mathematical creative thinking skills and early mathematical abilities, interview guidelines, and researchers as key instruments. Activities in this data analysis include data reduction, data display, and verification. The validity test of this research uses triangulation. This study shows that students' mathematical creative thinking skills are still lacking in indicators of flexibility, smoothness, and originality, especially in students with low initial ability.